2005
DOI: 10.1185/030079905x43631
|View full text |Cite
|
Sign up to set email alerts
|

Imipenem/cilastatin versus piperacillin/tazobactam plus amikacin for empirical therapy in febrile neutropenic patients: results of the COSTINE study

Abstract: The clinical effectiveness of I/C was similar to that of P/T+A. In both treatment groups toxicity was low and did not limit antibiotic therapy. Resource consumption was lower with I/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…In contrast, piperacillin/tazobactam (87.3%) and ciprofloxacin (61.8%) were the most frequently used initial antimicrobials in our NDE group. Previous studies have suggested that piperacillin/tazobactam and imipenem/cilastatin have similar efficacy and safety profiles [28-30]. Only one patient had ESBL-producing Enterobacteriaceae, and broad-spectrum antimicrobials may have different sensitivity patterns at other centers.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, piperacillin/tazobactam (87.3%) and ciprofloxacin (61.8%) were the most frequently used initial antimicrobials in our NDE group. Previous studies have suggested that piperacillin/tazobactam and imipenem/cilastatin have similar efficacy and safety profiles [28-30]. Only one patient had ESBL-producing Enterobacteriaceae, and broad-spectrum antimicrobials may have different sensitivity patterns at other centers.…”
Section: Discussionmentioning
confidence: 98%
“…75 A more recent study of febrile neutropenic patients reported that overall treatment costs were 189.55 euros less with imipenem than piperacillin/tazobactam (P < 0.001). 155 Imipenem monotherapy has been recommended in polymicrobial infections where combination therapy would be more costly, although imipenem combination therapy was recommended if Pseudomonas was present. 85 This sustained susceptibility, efficacy, tolerability and cost-effectiveness are the hallmarks of appropriate initial therapy.…”
Section: De-escalation Therapymentioning
confidence: 99%
“…Broad-spectrum antipseudomonal cephalosporins (such as ceftazidime [7] and cefepime [8][9][10][11][12][13][14]), carbapenems (such as imipenem-cilastatin [15,16] and meropenem [17][18][19][20][21][22][23][24][25][26][27][28][29]), and b-lactam-b-lactamase inhibitor combinations (such as ticarcillin clavulanate [13,30,31] and piperacillintazobactam [10,17,[32][33][34][35][36][37]) have been evaluated as monotherapy in this setting. The Spanish and German guidelines support choices from each antibiotic class, whereas the American guidelines have not recommended b-lactam-b-lactamase inhibitor agents, such as piperacillin-tazobactam, as monotherapy, citing limited experience with these agents when the guidelines were published in 2002 [2].…”
mentioning
confidence: 99%